Data for Danish speakers' assignment of stød in morphologically complex nonce words - Høeg, Annika (Stockholm University, 2026)
The dataset contains:
1) A data file in csv format with annotations of the occurrence of stød in 24 different nonce stems read in nine different morphological contexts (i.e. 216 different nonce words) by 49 Danish speakers. The morphological contexts are one of three suffixes (infinitive, present tense or agent noun) combined with one of three compound types (not compound, compound with a noun as the first member or compound with a preposition as the first member).
2) A R-markdown file with the code used for statistical analysis and visualization of the data.
3) A file with the carrier sentences that the nonce words in present tense and agent nouns were read in.
4) A text file with the Python code that were used to generate the nonce words.

Datasetet innehåller:
1) En datafil i csv-format med annoteringar av förekomsten av stød i 24 olika nonsensstammar, upplästa i nio olika morfologiska kontexter (dvs. 216 olika nonsensord) av 49 danska talare. De morfologiska kontexterna utgörs av en av tre suffix (infinitiv, presens eller nomen agentis) kombinerat med en av tre sammansättningstyper (inte sammansatt, sammansättning med ett substantiv som första led eller sammansättning med en preposition som första led).
2) En R Markdown-fil med kod som användes för statistisk analys och visualisering av data.
3) En fil med carrier sentences som nonsensorden i presens och nomen agentis lästes i.
4) En textfil med den Python-kod som användes för att generera nonsensorden.
Data for Danish speakers' assignment of stød in morphologically complex nonce words
Keywords: phonology; fonologi; prosody; prosodi; Danish language; danska; Stød; Stød; Nonce words; Nonsensord; Language and linguistics; Språk och lingvistik; Comparative Language Studies and Linguistics; Jämförande språkvetenskap och allmän lingvistik; Studies of Specific Languages; Studier av enskilda språk